Comparative Analysis of Microbiome in Nasopharynx and Middle Ear in Young Children With Acute Otitis Media - Xu, Qingfu; Gill, Steve; Xu, Lei; Gonzalez, Eduardo; Pichichero, Michael E. (Frontiers in Genetics, 2019)
Acute otitis media (AOM) is the most common pediatric infection for which antibiotics are prescribed in the United States. The role of the respiratory tract microbiome in pathogenesis and immune modulation of AOM remains unexplored. We sought to compare the nasopharyngeal (NP) microbiome of children 1-3 weeks prior to onset of AOM vs. at onset of AOM, and the NP microbiome with the microbiome in middle ear (ME). Six children age 6-24 months old were studied. Nasal washes (NW) were collected at healthy visits 1-3 weeks prior to AOM and at onset of AOM. The middle ear fluids (MEF) were collected by tympanocentesis at onset of AOM. Samples were stored in Trizol reagents or PBS at -80oC till use. The microbiome was characterized by 16S rRNA gene sequencing. Taxonomic designations and relative abundance of bacteria were determined using the RDP classifier tool through Quantitative Insights Into Microbial Ecology (QIIME). Cumulative sum scaling (CSS) normalization was applied before determining bacterial diversity and abundance. Shannon diversity index was calculated in Microsoft excel. The relative abundance of each bacteria species was compared via Mann Whitney U test. We found that the NW microbiome of children during healthy state or at baseline was more diverse than microbiome during AOM. At AOM, no significant difference in microbiome diversity was found between NW and MEF, although some bacteria species appear to differ in MEF than in NW. The microbiome of samples stored in PBS had significant greater diversity than samples stored in Trizol reagent.